DESIGN AND DEVELOPMENT OF AN E-MODULE FOR VOCABULARY LEARNING IN JUNIOR HIGH SCHOOLS - Syahrianita Syahrianita; Kalsum Kalsum (Al-Irsyad: Journal of Education Science, 2025)
This study examines the design, development, and effectiveness of "Easy Vocabulary," a web-based e-module aimed at improving English vocabulary skills among junior high school students at SMPN 1 Parepare, Indonesia. Addressing challenges like limited learning resources, traditional teaching methods, and lack of interactive media, the study applied the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and utilized a one-group pretest-posttest design involving 32 Grade VIII students (aged 13-14 years) selected through purposive sampling. The e-module features locally contextualized content, multimedia elements like barcode-integrated audio pronunciation, and web-based accessibility for independent learning. Expert validation from material experts, media specialists, teachers, and students yielded high validity scores: material expert (92.5%), media expert (81%), teacher (85.55%), and student responses (82.29%). Effectiveness was evident in the significant improvement in vocabulary mastery, with pretest scores of 57.75 increasing to 93.90 posttest, achieving an N-Gain score of 0.85, indicating high effectiveness. The study’s success is attributed to the combination of contextual design, interactive multimedia, and culturally relevant content, fostering student engagement. This research contributes valuable insights to the literature on educational technology, offering a replicable framework for enhancing vocabulary learning in Indonesian educational settings.